C8‐BTBT‐C8 Thin‐Film Transistors Based on Micro‐Contact Printed PEDOT:PSS/MWCNT Electrodes. (2nd February 2023) - Gubanov, Kirill; Johnson, Manuel; Akay, Melda; Wolz, Benedikt C.; Shen, Dan; Cheng, Xing; Christiansen, Silke; Fink, Rainer H.
Abstract: Advances in organic materials manufacturing have enabled the creation of electronic devices using solution‐processing techniques by employing soluble materials with high conductivity grade. In this exploratory study, the use of micro‐contact for poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) polymer ink deposition as high‐quality structured electrodes for organic field‐effect transistors (OFETs) in top‐contact geometry is demonstrated. The optimized OFET's solution‐processed fabrication is a promising strategy to be realized in the simple, cost‐effective roll‐to‐roll manufacturing processes. The electrical performance of the fabricated devices is comparable to transistors with gold electrodes prepared via vacuum deposition, and even exceeding the values of the charge carriers' mobilities and featuring lower contact resistance ( R c ), due to lower charge‐carrier injection barrier for carbon‐based organic electrodes. An addition of multi‐walled carbon nanotubes to the PEDOT:PSS decreases R c even further, changing the work function for better energy alignment with semiconductor materials. Abstract : Microstructured source and drain poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) electrodes are prepared onto spin‐cast C8 ‐BTBT‐C8 films using microcontact printing. Only the precise control of the pressure yields high structural quality of the deposited electrodes. The addition of multi‐walled carbon nanotubes to the PEDOT:PSS ink leads to a significant reduction of contact resistance thus optimizing charge‐carrier injection and device performance.